2019
DOI: 10.1038/s41598-019-43141-6
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas9 Editing in Maize: Systematic Evaluation of Off-target Activity and Its Relevance in Crop Improvement

Abstract: CRISPR-Cas9 enabled genome engineering has great potential for improving agriculture productivity, but the possibility of unintended off-target edits has evoked some concerns. Here we employ a three-step strategy to investigate Cas9 nuclease specificity in a complex plant genome. Our approach pairs computational prediction with genome-wide biochemical off-target detection followed by validation in maize plants. Our results reveal high frequency (up to 90%) on-target editing with no evidence of off-target cleav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 80 publications
2
61
0
1
Order By: Relevance
“…Several recent works have shown CRISPR-mediated targeted recombination in Drosophila (Brunner et al 2019), yeast (Sadhu et al 2016), and tomato (Filler-Hayut et al 2017). Studies have shown that design of gRNAs with at least three mismatches from other genomic regions can alleviate off-target editing (Young et al 2019). Polymorphism of TAS4a locus in 101-14 rootstock genotype appears to reduce the number of mismatches to two residues compared to the Pinot Noir reference genome, and thus likely made the locus more prone to off target activity by TAS4b gRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent works have shown CRISPR-mediated targeted recombination in Drosophila (Brunner et al 2019), yeast (Sadhu et al 2016), and tomato (Filler-Hayut et al 2017). Studies have shown that design of gRNAs with at least three mismatches from other genomic regions can alleviate off-target editing (Young et al 2019). Polymorphism of TAS4a locus in 101-14 rootstock genotype appears to reduce the number of mismatches to two residues compared to the Pinot Noir reference genome, and thus likely made the locus more prone to off target activity by TAS4b gRNA.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of CRISPR-CAS9 tools recognizing different PAMs (Hua et al 2019), the range of nucleotides accessible to BECAS9 will also expand, giving rise to a large set of genome editing tools for deciphering gene functions in detail. Although offtarget activity of SpCAS9 has been described in most eukaryotes and is highly variable depending on the sgRNA designed (O'Geen et al 2015;Tsai and Joung 2016), it seems that off-target mutations are rare in plants and can almost always be predicted in silico Tang et al 2018;Young et al 2019), even if there is still debate regarding the level of off-target activity in plants . Far fewer data are available concerning the off-target activity of LbCPF1, but the situation seems similar to that of SpCAS9 (Tang et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The off-site targeting in plant can be avoided through evaluating and predicted using various web-based tools such as Cas-OFFinder (Bae et al, 2014), CROP-IT (Singh et al, 2015), CRISPOR (Haeussler et al, 2016), and other soft tools (Hahn and Nekrasov, 2019). The effect can be reduced by improving specificity of CRISPR system using high-fidelity SpCas9 variants (Zhang et al, 2017;Zhong et al, 2019), nCas9 (nickase) with two sgRNAs (Shen et al, 2014;Zhang et al, 2015), delivering purified Cas9 ribonucleoproteins (RNPs) into cells (Kim et al, 2017;Andersson et al, 2018), and modified sgRNA (Young et al, 2019). For soybean, there has been a system established for the scientific society to shared genome-wide databases and to identify off site targets (Zou et al, 2020).…”
Section: Off-site Targetingmentioning
confidence: 99%